Longitudinal elastic nonlinearity of compositematerial - B.N. Fedulov; D.A. Bondarchuk; E.V. Lomakin (Fracture and Structural Integrity)
It is known that the initial waviness of the fiber affects the stiffness characteristics and strength of the polymer composite material. The article presents a continuum model taking into account the nonlinearity of the longitudinal stiffness of the unidirectional composite. In this study, a finite element experiment was conducted to investigate the variations in the longitudinal stiffness of the composite material subjected to uniaxial compression. The experiment considered a range of different degree of fibers waviness to comprehensively examine the impact on the material's stiffness. Obtained results explain the difference in stiffness observed in fiber composites in the longitudinal direction under uniaxial tension and compression. Special constitutive relations proposed to model compressive stiffness reduction in longitudinal direction.